Procesy fuzji i przejęć w gospodarce światowej od końca XIX wieku do 2004 roku - Piasecka-Głuszak, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Globalization, increase of international competition and growth of significance of international companies - these are the factors that had among the others great influence on the increased number of mergers and acquisitions (M&A). M&A started to play a key role in strategies of many companies who strove for development, retaining and strengthening their market position and who saw opportunities in synergy effect. This article's objectives were to present various definitions of M&A, reasons and risks of M&A, classifications and in particular intensification stages and examples of M&A in global economy since the end of XIX century to 2004.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 272-281